A biophysical study on the mechanism of interactions of DOX or PTX with α-lactalbumin as a delivery carrier. Issue 1 (December 2018) - Delavari, Behdad; Mamashli, Fatemeh; Bigdeli, Bahareh; Poursoleiman, Atefeh; Karami, Leila; Zolmajd-Haghighi, Zahra; Ghasemi, Atiyeh; Samaei-Daryan, Samaneh; Hosseini, Morteza; Haertlé, Thomas; Muronetz, Vladimir I.; Halskau, Øyvind; et al.
Abstract Doxorubicin and paclitaxel, two hydrophobic chemotherapeutic agents, are used in cancer therapies. Presence of hydrophobic patches and a flexible fold could probably make α-Lactalbumin a suitable carrier for hydrophobic drugs. In the present study, a variety of thermodynamic, spectroscopic, computational, and cellular techniques were applied to assess α-lactalbumin potential as a carrier for doxorubicin and paclitaxel. According to isothermal titration calorimetry data, the interaction between α-lactalbumin and doxorubicin or paclitaxel is spontaneous and the K (M−1 ) value for the interaction of α-lactalbumin and paclitaxel is higher than that for doxorubicin. Differential scanning calorimetry and anisotropy results indicated formation of α-lactalbumin complexes with doxorubicin or paclitaxel. Furthermore, molecular docking and dynamic studies revealed that TRPs are not involved in α-Lac's interaction with Doxorubicin while TRP 60 interacts with paclitaxel. Based on Pace analysis to determine protein thermal stability, doxorubicin and paclitaxel induced higher and lower thermal stability in α-lactalbumin, respectively. Besides, fluorescence lifetime measurements reflected that the interaction between α-lactalbumin with doxorubicin or paclitaxel was of static nature. Therefore, the authors hypothesized that α-lactalbumin could serve as a carrier for doxorubicin and paclitaxel by reducing cytotoxicity and apoptosis which was demonstrated during ourin vitro cell studies.